The effect of dam nutrient deprivation on lamb carcass characteristics, retail yields, and nutrient composition - Brenman, Kristina Anne, author; Belk, Keith, advisor; Woerner, Dale, committee member; Engle, Terry, committee member; Mykles, Donald, committee member (Colorado State University. Libraries, 2012)
The objective of this study was to determine the effect of dam nutrient restriction on offspring carcass characteristics, retail cut yields, and nutrient composition. Forty one western white rams and ewes were obtained from a previous Colorado State University study of dam nutrient restriction. Prior to gestation, dams were fed 100% of their nutrient requirements. The diet of dams was a vitamin-mineral rich pelleted beet-pulp (77.8% total digestible nutrients [TDN], 90.0% dry matter [DM], and 9.4% crude protein [CP]). At 28 days gestational age, dams were randomly assigned to individual pens and separated into three different treatments: control (100% nutrient requirements), half ration (fed 50% of their nutrient requirements from day 28 until term), and realimented (fed 50% of their nutrient requirements from day 28 until day 78, and then slowly realimented back to 100% for the remainder of gestation). All twin lambs were slaughtered, and hot carcass weight, 12th rib fat, body wall thickness, adjusted fat, ribeye area, ribeye marbling, leg score, leg circumference, conformation, flank streaking, flank firmness, flank color, kidney fat weight, L*, a*, and b* were obtained. After all lambs were slaughtered, one half of each lamb carcass was fabricated in the following subprimals: rack, roast ready, frenched PSO 3x1" (IMPS 204C); shoulder, square-cut, boneless (IMPS 208); Denver ribs, skirt-off (IMPS 209A); Foreshank (IMPS 210); loin, short-cut, trimmed PSO 0x0" (IMPS 232A); flank untrimmed (IMPS 232E); leg, hindshank (IMPS 233F); and leg, shank-off, boneless (IMPS 234A). Lastly, all lambs were utilized to determine dry matter, moisture, crude protein, crude fat, ash, vitamins A and E, trace minerals, and fatty acids. No interactions were found between treatment and gender for any characteristic, so treatment and gender were analyzed separately. Lambs of ewes that were nutritionally restricted were smaller in size with less fat. Lambs of the realimented group had more fat than either the control or the half ration groups. Rams had more percent lean content than ewes, which was to be expected. Results of this study provide insight on the effect of nutrient restriction on lamb growth and development, as well as nutrient content of American lamb.
Keywords: nutrient restriction; nutrient composition; retail cuts; carcass characteristics; lamb